A STUDY OF ION BOMBARDMENT TIME FOR COPPER SPUTTERING BY USING AN ARGON – ARC PLASMA - Yahya, Khalid; Al-Ani, Riayhd; Mazher, Sabah (Iraqi Journal of Science, 2024)
An experimental investigation is carried out to study argon ion bombardment time for a disk sputtering pole which is made from pure copper of diameter 30 mm and impacted by argon ions of energy 120 eV. This ions are generated by magnetically confined ion source . The ion source consists of a tungsten filament of 0.2 mm diameter as a cathode pole, and a graphite plate with a slot which represents the anode pole , and the arc of plasma which confined by a homogeneous magnetic field .A set of experiments are conducted to collect the sputtering copper atoms on a slab , for different values of argon ion densities and bombardment times . The results of the study show that the net mass of collective sputtered atoms and the thickness of layer are increasing as the bombardment time increases , and reach 273.2 mgm and 24.39 μm respectively for argon ion density 7x1018 m-3 and bombardment time 60 min